PENGEMBANGAN STRATEGI CRITICAL INCIDENT BERBANTUAN MEDIA BLOG DALAM PEMBELAJARAN MENULIS TEKS CERITA PENDEK DI SEKOLAH MENENGAH PERTAMA - Riska Novia Matalata, - (2020)
The main background of this research is focussing on the lack of short story writing skills and learning strategies in school. Based on that problem, this research tries to develop one of the critical incident strategies which assisted by blog media to learn to write a short story. The purposes are to create appropriate learning strategies that integrate with the students learning process and teachers' teaching. There are five discussions in this research: 1) The learning profile of short-story writing; 2) The design; 3) Developing; 4) The effectivity and 5) The responses or feedbacks of the students on this strategy. The method used in this research is Research & Development by using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Data collection techniques were done by questionnaires, observations, and exam results. This study also conducted a t-test to determine the effectiveness of the critical incident strategy assisted by Blog media in learning to write short story. Based on the t test, this research showed that the development of critical incident strategies assisted by blog media is effective and has positive responses. Based on the research findings, it is recommended that teachers specifically use the Critical Incident strategy, especially in the step of thinking strategy because it could improve the learning of short story writing for students.